SPEECH ACTS OF CROWN PRINCE MOHAMMED BIN SALMAN SPEECH ON FUTURE INVESTMENT INITIATIVE IN 2018, AND ITS IMPACT ON SAUDI IDEOLOGY - Suha Abdullah Alharbi (IKIP Siliwangi, 2023)
The goal of this study is to analyze the types of illocutionary acts, which were dominantly used by Crown Prince Mohammed bin Salman's speech and how they affected Saudi youth ideology. The data is obtained by translating and transcribing the speech, then analyzed through Searle’s (1969) speech acts theory. A questionnaire was held to show the effectiveness of His Highness’s speech on Saudi youth. The findings showed that most types of illocutionary acts that Crown Prince Mohammed bin Salman used were representative (61 times) 73.5%. Then Commissive was eleven times (13.3%). The questionnaire results showed that many Saudi youths strongly agreed that Crown Prince Mohammed bin Salman's speech positively affected their mentality, and this was reflected in their professional lives. Keywords: Pragmatics; Speech Acts; Speech